Christian theologies of Scripture : a comparative introduction - Holcomb, Justin S., 1973- (NYU Press, 2006)
All religious traditions that ground themselves in texts must grapple with certain questions concerning the texts' authority. Yet there has been much debate within Christianity concerning the nature of scripture and how it should be understood--a debate that has gone on for centuries. Christian Theologies of Scripture traces what the theological giants have said about scripture from the early days of Christianity until today. It incorporates diverse discussions about the nature of scripture, its authority, and its interpretation, providing a guide to the variety of views about the Bible through.